2013
DOI: 10.1080/07315724.2013.793580
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Supplementation During Resistance Training Augments Lean Body Mass

Abstract: Despite consuming similar calories and protein during resistance training, daily supplementation with whey was more effective than soy protein or isocaloric carbohydrate control treatment conditions in promoting gains in lean body mass. These results highlight the importance of protein quality as an important determinant of lean body mass responses to resistance training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
5
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(183 citation statements)
references
References 27 publications
9
156
5
11
Order By: Relevance
“…In the present study, we provided milk proteins as the source of dietary nitrogen in the postexercise beverages given that they are complete, high-quality proteins that are generally associated with greater muscle remodeling and recovery after exercise in adults (32). For example, studies in adults have revealed that milk and associated dairy-based proteins (especially whey) support greater rates of muscle protein synthesis and net protein balance after exercise compared with plantbased proteins such as soy (38,46), which can ultimately translate into greater training-induced gains in muscle and lean body mass (20,44). The greater anabolic effect of dairy compared with soy protein in adults occurs despite these sources having similarly high [albeit artificially truncated (37)] protein quality ratings according to the protein digestibilitycorrected amino acid score (32).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we provided milk proteins as the source of dietary nitrogen in the postexercise beverages given that they are complete, high-quality proteins that are generally associated with greater muscle remodeling and recovery after exercise in adults (32). For example, studies in adults have revealed that milk and associated dairy-based proteins (especially whey) support greater rates of muscle protein synthesis and net protein balance after exercise compared with plantbased proteins such as soy (38,46), which can ultimately translate into greater training-induced gains in muscle and lean body mass (20,44). The greater anabolic effect of dairy compared with soy protein in adults occurs despite these sources having similarly high [albeit artificially truncated (37)] protein quality ratings according to the protein digestibilitycorrected amino acid score (32).…”
Section: Discussionmentioning
confidence: 99%
“…Protein ingested soon after a resistance training session amplifies the resulting increase in muscle protein synthesis; the anabolic signal imparted by the exercise session is potentiated by leucine-mediated mTORC1 activation (Esmarck et al 2001;Breen and Phillips 2012;Burd et al 2012;Volek et al 2013). Hence, postexercise supplementation with 2-3 g of leucine (or ingestion of an equivalent amount from leucine-rich protein, such as whey), along with some carbohydrate to further enhance mTORC1 activity (via insulin), may have potential as an adjuvant to resistance training for prevention of sarcopenia.…”
Section: Dietary Leucine Promotes Anabolism By Stimulating Mtorc1 Actmentioning
confidence: 99%
“…Intervention with the hydrolysed whey protein resulted in significant reduction in the muscle damage markers (creatine kinase and lactate dehydrogenase) (Lollo et al 2014). Muscle mass growth by daily consumption of whey protein was compared with that of soy protein, using a randomized study on subjects undergoing resistance exercise (Volek et al 2013). Lean body mass gains were significantly high in whey protein than soy protein group and the remarkable response was correlated with the elevated levels of leucine and faster absorption.…”
Section: Resistance Exercise and Muscle Synthesismentioning
confidence: 99%